The role of fertilizers in transforming agriculture in the Kyrgyz Republic - Abdulhamidov, Dilshod (International Food Policy Research Institute, 2014)
The Republic of Kyrgyzstan is a landlocked country where nearly 65 percent of the population lives in rural areas. Wheat is the staple crop in Kyrgyzstan; however, average wheat yields were just 2.4 metric tons (MT)/ha as of 2013, which is well below potential yield estimates of 5.5 MT/ ha. The country is classified by the UN FAO as a low-income, food-deficit country that relies on wheat imports from Kazakhstan and Russia to cover 25 percent of its consumption requirements. Agriculture contributes 20.8 percent of GDP and more than 1 million smallholder households are involved in the agriculture sector. Agriculture in the northern region of the country is more industrialized, with farm activities fully mechanized compared to the southern region. The south is highly populated, but the availability of arable land is limited.